Development of rainfall model for flood level simulation incorporating tidal effects / Mohd Adib Mohammad Razi - Mohammad Razi, Mohd Adib (Institute of Graduate Studies, UiTM, 2014)
Flood simulation models that have been developed in these decades are mostly influenced by local factors. Building a good flood model begins with determining the amount of rainfall that is influenced by local meteorology; and this model can estimate the rainfall pattern in the next catchment area, in which the runoff will flow to the ocean. However, most of the developed models are not capable of merging the whole hydrologic cycle, where the models should incorporate rainfall models with meteorological parameters. This step is very important as to first, project the amount of rainfall in a particular catchment area, considering the overall hydrologic model and second, to identify the areas with flood risks, considering the tidal effect. In order to fix the shortcoming, this study introduces a rainfall model that has been developed using selected rainfall parameters with the aim to recognize rainfall depth in a catchment area. In order to examine its ability, the rainfall model will be integrated with selected hydrologic models after the development phase. The result will influence quantity of flood in the catchment area, if a flood simulation model that considers every factor in hydrologic cycle were to be developed.